Ke arah perindustrian negara Islam berasaskan moral dan nilai - Hashim, Rosnani (Institut Pengajian Ilmu-Ilmu Islam (IPI-ABIM), 1998)
This article presents a brief critique of the concept of industrialization in the Western perspective. It argues that industrialization based on the Western perspective has brought some good but more harm to mankind, especially with respect to family unit and the environment. The author argues and asserts that industrialization that is based on Islamic principles, moral and ethical values will be more able to provide growth, development and prosperity to human kind. Among others, this article discusses briefly utilitarianism which emphasizes materialism and secularism as the backbone of Western industrialization. It examines the effect of Western Industrialization programmes which, in addition to producing sophisticated technological gadgets, had also given rise to social confusion, the environmental crisis and the crisis of values. It also presents the Islamic concept and principles of industrialization based on the concept of tazkiyah (purification) which include the principles of tawhid (oneness of God), khilafah (vicegerency), amanah (trust), ‘ilm (knowledge), shari’ah (Law), ‘ibadah (worship), ‘adl (justice) and istihsan (excellence) and istislah (public interest).